FLASH early science - discovery of an intervening HI 21-cm absorber from an ASKAP survey of the GAMA 23 field - Allison, JR; Sadler, EM; Bellstedt, S; Davies, LJM; Driver, SP; Ellison, SL; Huynh, M; Kapinska, AD; Mahony, EK; Moss, VA; Robotham, ASG; Whiting, MT; et al. (Oxford University Press, 2020)
We present early science results from the First Large Absorption Survey in H I (FLASH), a spectroscopically blind survey for 21-cm absorption lines in cold hydrogen (H I) gas at cosmological distances using the Australian Square Kilometre Array Pathfinder (ASKAP). We have searched for H I absorption towards 1253 radio sources in the GAMA 23 field, covering redshifts between z = 0.34 and 0.79 over a sky area of approximately 50 deg2. In a purely blind search, we did not obtain any detections of 21-cm absorbers above our reliability threshold. Assuming a fiducial value for the H I spin temperature of Tspin = 100 K and source covering fraction cf = 1, the total comoving absorption path-length sensitive to all Damped Lyman α Absorbers (DLAs; NH I ≥ 2 × 1020 cm−2) is ΔX = 6.6 ± 0.3 (Δz = 3.7 ± 0.2) and super-DLAs (NH I ≥ 2 × 1021 cm−2) is ΔX = 111 ± 6 (Δz= 63 ± 3). We estimate upper limits on the H I column density frequency distribution function that are consistent with measurements from prior surveys for redshifted optical DLAs, and nearby 21-cm emission and absorption. By cross-matching our sample of radio sources with optical spectroscopic identifications of galaxies in the GAMA 23 field, we were able to detect 21-cm absorption at z = 0.3562 towards NVSS J224500−343030, with a column density of NHI=(1.2±0.1)×1020(Tspin/100K) cm−2. The absorber is associated with GAMA J22450.05−343031.7, a massive early-type galaxy at an impact parameter of 17 kpc with respect to the radio source and which may contain a massive (MH I ≳ 3 × 109 M⊙) gas disc. Such gas-rich early types are rare, but have been detected in the nearby Universe.